Classification Systems for Digital Era - Gopinath, M. A. (Journal of Information and Knowledge, 2001)
Digital Technologies and telecommunication systems have revolutionised developments in information systems. Under these circumstants, how a flexible classification system can influence the knowledge organization and decision support systems is discussed in the paper. It is also shown how the classification and indexing may be like beyond 2001 AD.